Smart 131I‐Labeled Self‐Illuminating Photosensitizers for Deep Tumor Therapy. (26th August 2021) - Guo, Jingru; Feng, Kai; Wu, Wenyu; Ruan, Yiling; Liu, Huihui; Han, Xiuping; Shao, Guoqiang; Sun, Xiaolian
Abstract: Stimulating photosensitizers (PS) by Cerenkov radiation (CR) can overcome the light penetration limitation in traditional photodynamic therapy. However, separate injection of radiopharmaceuticals and PS cannot guarantee their efficient interaction in tumor areas, while co‐delivery of radionuclides and PS face the problem of nonnegligible phototoxicity in normal tissues. Here, we describe a 131 I‐labeled smart photosensitizer, composed of pyropheophorbide‐a (photosensitizer), a diisopropylamino group (pH‐sensitive group), an 131 I‐labeled tyrosine group (CR donor), and polyethylene glycol, which can self‐assemble into nanoparticles ( 131 I‐sPS NPs). The 131 I‐sPS NPs showed low phototoxicity in normal tissues due to aggregation‐caused quenching effect, but could self‐produce reactive oxygen species in tumor sites upon disassembly. Upon intravenous injection, 131 I‐sPS NPs showed great tumor inhibition capability in subcutaneous 4T1‐tumor‐bearing Balb/c mice and orthotopic VX2 liver tumor bearing rabbits. We believed 131 I‐sPS NPs could expand the application of CR and provide an effective strategy for deep tumor theranostics. Abstract : Novel responsive nanoparticles based on Cerenkov resonance energy transfer are suitable for photodynamic therapy (PDT) of deep tumors without the need for exogenous light. The nanoparticles have low toxicity and few harmful side effects on normal tissue.